New approaches to teaching History of Kazakhstan in High schools in the second decade of the XXI c. (Journal of history, 2020)
In this paper I argue that History of Kazakhstan still have to be a com- pulsory subject for all Kazakhstani students. But challenges of time requires constructing the course on the new principles based on the explicit aim– influence to forming historical thinking of the youth and increasing their civic competencies. Competency in historical thinking skills enables stu- dents to think critically and creatively, to understand historical criteria, but also to develop their academic skills.